KẾT QUẢ ỨNG DỤNG CHẾ PHẨM PEPTIT ĐIỀU HÒA SINH HỌC HỖ TRỢ ĐIỀU TRỊ NÂNG CAO SỨC KHỎE CHO NẠN NHÂN CHẤT ĐỘC DA CAM / DIOXIN BỊ SUY GIẢM MIỄN DỊCH - Hoàng, Văn Huấn; Phạm, Khắc Linh; Nguyễn, Như Nghĩa (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE RESULT OF USING PEPTIDES BIOREGULATORS SUPPORTING THE TREATMENT FOR THE PERSON WHO GET IMMUNE DEFICIENCY DUE TO EXPOSING TO AGENT ORANGEThe article provides some results of researching in supporting the treatment and rehabilitation for verterans who get immune deficiency because of exposing to Agent Orange by the peptides bioregulator produced by Russia Federation. The research shows that the good result of peptides bioregulator application occupies 70%, the goodish one account for 30% and there is complete no negative result. The peptides bioregulator products effect to immune system to increase the immune indexes: IgG, IgM, CD3, CD4 and CD8. The peptides bioregulator products assist veterans treat and improve their health and raise immune ability up without any side effect.